Simulation Analysis of Churning Loss of Internal Cavity Structure of Gearbox based on MPS Method - Dong Guo; Dongyuan Luo; Fangchao Chen (Jixie chuandong)
In order to explore the influence of the internal cavity structure on the churning loss and to improve the efficiency of the automobile transmission system，the gearbox is used as the research object，and a numerical simulation model of the gearbox churning loss is established by using the moving particle semi-implicit method. Through the numerical simulation results and combined with the distribution of lubricants，the influence of different axial clearances，radial clearances，oil baffle plates，oil collection grooves and internal cavities on the churning loss is analyzed. The analysis results show that the churning loss has a non-linear positive correlation with the axial clearance，but when the axial clearance reaches a certain value，it has almost no effect on the churning loss； it has a nonlinear negative correlation with the radial clearance，and as the radial clearance increases，its downward trend becomes smaller； the oil baffle and oil collecting groove structure can reduce the churning loss，and with the increase of its length，the effect becomes more significant； the streamlined cavity and the arc-shaped cavity increase the churning loss to a certain extent.